The Linguistic Al-Qur'an And Linguistic Approach In Interpretation Of The Al-Qur'an - Irawan, Bambang (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
Abstract This article describes a linguistic approach in interpreting the holy book of the Al-Qur'an. In this case, attempting of systematizing theories are used in the interpretation of the linguistic to the position in the place that is found the exact meaning. From the result of the study is found that the linguistic position is in the realm of Qur'an interpretation can be seen from two aspects, as the theological argument and language is as the language of the methodological. language is manifest a code of values that is fought by al- Qur’an. The language of the Qur'an is sacred code system God, holy and sublime, human or system code of profane, historical, and cultural. Moreover, the second, The first meaning it is presupposed that the language is usually manifest in the rules and culture. Keyword: Linguistics, Interpretation Al-Qur’an